2017
DOI: 10.1016/j.nedt.2016.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Using simulation to improve the capability of undergraduate nursing students in mental health care

Abstract: This study provides evidence to support the use of simulation to enhance student nurses' clinical capabilities in providing mental health care in acute care environments. Nursing curriculum development should be based on best-evidence to ensure that future nursing graduates have the skills and capability to provide high-quality, holistic care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 34 publications
2
20
0
1
Order By: Relevance
“…The students in this study reported an increased level of preparedness for their clinical placement after the MHS, specifically in relation to their ability to interact with and provide care to consumers experiencing a mental illness. The impact of a MHS on student confidence was previously identified by Kunst et al (2017). In this study, student’s responses on the post‐test responses improved substantially after completing the workshop.…”
Section: Discussionmentioning
confidence: 77%
“…The students in this study reported an increased level of preparedness for their clinical placement after the MHS, specifically in relation to their ability to interact with and provide care to consumers experiencing a mental illness. The impact of a MHS on student confidence was previously identified by Kunst et al (2017). In this study, student’s responses on the post‐test responses improved substantially after completing the workshop.…”
Section: Discussionmentioning
confidence: 77%
“…High fidelity web-based simulation can be used to teach undergraduates to recognise the deteriorating patient (Cooper et al, 2012) and a simulated "live" setting in a laboratory can allow mental health nursing students to increase their ability to recognise physical deterioration in a patient (Chadwick & Withnell, 2016). High fidelity simulation has been used to teach students how to undertake an alcohol withdrawal assessment following possible deliberate self harm in the ED setting (Kunst, Mitchell & Johnston, 2017).…”
Section: Types Of Simulation Materials Availablementioning
confidence: 99%
“…While simulation-based education has increased in both extent and scope in many nursing education programmes in Europe, the USA, Asia, the Middle East and Australia, the literature shows a lack of implementation and research on simulation in low-and middle-income countries [2,[8][9][10][11][12][13][14]. To the best of our knowledge, no studies have highlighted simulation-based education in nursing education programmes in Sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%